2017
DOI: 10.3102/0002831217732000
|View full text |Cite
|
Sign up to set email alerts
|

Will Public Pre-K Really Close Achievement Gaps? Gaps in Prekindergarten Quality Between Students and Across States

Abstract: Publicly funded pre-K is often touted as a means to narrow achievement gaps, but this goal is less likely to be achieved if poor and/or minority children do not, at a minimum, attend equal quality pre-K as their non-poor, non-minority peers. In this paper, I find large “quality gaps” in public pre-K between poor, minority students and non-poor, non-minority students, ranging from 0.3 to 0.7 SD on a range of classroom observational measures. I also find that even after adjusting for several classroom characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 54 publications
0
41
0
Order By: Relevance
“…Valentino looks at whether publically funded pre‐K programs have the potential to reduce the achievement gap by reducing disparities in skill among students kindergarten. This research shows that although these programs are often designed to reduce inequality by improving the skills of minority students, “disadvantaged students attended public preschools that were far inferior to those available to their more advantaged peers (Valentino, , p. 110, emphasis in original).” Thus, even a policy that is ostensibly designed to reduce the achievement gap can exacerbate disparities by providing White students with additional opportunities.…”
Section: Discussionmentioning
confidence: 95%
“…Valentino looks at whether publically funded pre‐K programs have the potential to reduce the achievement gap by reducing disparities in skill among students kindergarten. This research shows that although these programs are often designed to reduce inequality by improving the skills of minority students, “disadvantaged students attended public preschools that were far inferior to those available to their more advantaged peers (Valentino, , p. 110, emphasis in original).” Thus, even a policy that is ostensibly designed to reduce the achievement gap can exacerbate disparities by providing White students with additional opportunities.…”
Section: Discussionmentioning
confidence: 95%
“…Each of these family, school, and neighborhood factors may independently affect academic performance, but their effects may interact as well. For example, low-income communities may have lower average achievement than high-income communities not only because poor families can afford to provide their children with fewer educational resources at home but also because concentrated poverty may lead to lower quality preschool options (Valentino, 2017) and lower quality public K–12 schools. High-income communities, where parents can afford to pay for high-quality childcare and preschool, may also be able to attract more skilled K–12 teachers (Lankford, Loeb, & Wykoff, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…High-quality early childhood opportunities can improve a child’s short- and long-term outcomes (e.g., Phillips et al, 2017), yet quality is highly variable among ECE programs (Morris et al, 2018; Yoshikawa et al, 2013). Prior research has explored which children attend lower versus higher quality care (i.e., Bassok & Galdo, 2016; Valentino, 2018). Studies have also examined factors that drive families ECE choices and identified supply and cost as major drivers (e.g., Chaudry et al, 2011; Sandstrom et al, 2012), with some indications of informational or logistical barriers for disadvantaged families (Shapiro et al, 2019).…”
Section: Prior Literaturementioning
confidence: 99%